The impact of university openings on local youth - Friederike Hertweck; Serife Yasar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
This study investigates how the establishment of a new university affects the educational pathways for younger cohorts. By analyzing cohorts at various stages of their education, we show a notable shift towards higher education and a decline in completion rates for vocational training programs across all cohorts. This effect is observed even among adolescents in upper secondary school, despite the apparent pre-determination of their educational trajectory. However, the benefits are not distributed equally, with youth from academic households experiencing the most significant gains, which raises concerns about increasing educational inequalities due to new university establishments. Our results highlight the complex interplay between accessibility, social networks, and educational preferences, calling for policy interventions that balance the expansion of higher education access with efforts to mitigate increased stratification. – – Die vorliegende Studie befasst sich mit den Auswirkungen von Universitätsgründungen auf die Bildungsverläufe jüngerer Kohorten. Die Analyse zeigt eine signifikante Verschiebung hin zur Hochschulbildung sowie einen Rückgang der Ausbildungsquoten in allen Schulkohorten. Dieser Effekt zeigt sich sogar bei Jugendlichen in der gymnasialen Oberstufe, obwohl deren Bildungsentscheidungen eigentlich bereits gefallen sein sollten. Allerdings ist der Nutzen ungleich verteilt: Jugendliche aus Akademikerhaushalten profitieren am stärksten, was darauf hindeutet, dass die Einrichtung neuer Hochschulen die Bildungsungleichheit verstärkt. Unsere Ergebnisse verdeutlichen das komplexe Zusammenspiel von Zugang, sozialen Netzwerken und Bildungspräferenzen und fordern politische Maßnahmen, die eine Ausweitung des Hochschulzugangs mit Anstrengungen zur Verringerung der zunehmenden Bildungsungleichheit in Einklang bringen.
Keywords: I2; R23; 330; Education expansion; educational choices; human capital; educational aspirations; university openings